HUBUNGAN TINGKAT KECEMASAN TERHADAP PERFOMANCE ATLET DAYUNG CANOEING - setiawan, fadhilah; Pudjijuniarto, Pudjijuniarto (Kesehatan Olahraga, 2022)
Abstract Rowing is a sport using water media that requires endurance, physical strength, technique, concentration and psychology. In the canoeing number, there is a decrease in performance during training and competing. It can have an effect on the quality of rowing athletes in achieving achievements. This study aims to determine the relationship of anxiety levels to the performance of canoeing rowing athletes. In this study using quantitative descriptive research methods with correlation test. This study consisted of two variables, namely: Anxiety, and the performance of canoeing rowing athletes. The population in this study was barbossa Paddle Club canoeing rowing athletes totaling 20 people (12 Men and 8 Women). The use of the sample used purposive sampling technique with a sample of 10 people consisting of 6 men and 4 women. Based on the results of this study, it can be concluded that there is a very strong relationship between the level of anxiety and the performance of canoeing rowing athletes (r = 0,856) Keywords: Anxiety, Performance, Rowing